Molecular Structure, Molecular Docking and Absorption, Distribution, Metabolism, Excretion and Toxicity study of Cellulose II - Çelik, Sefa; Demirağ, Aliye Demet; Özel, E. Ayşen; AKYÜZ, SEVİM (Wiley-VCH Verlag GmbH, 2021)
Cellulose is a renewable biopolymer which is the most abundant in nature, formed by binding of glucose units with beta-1,4 glycosidic bonds. Cellulose is divided into two groups as bacterial cellulose (BC) and vegetable cellulose. This study reports the interaction mechanism of Cellulose II, which is a BC, with the cellulase enzymes, determined by molecular docking method based on key-lock theory. The most stable molecular geometry of the Cellulose II molecule was determined by density functional theory using Gaussian 09 program. The scaled vibration frequencies of optimized geometry were calculated by using Molvib program. Molecular electrostatic potential and frontier molecular orbital analyses were performed. Molecular interactions between cellulose II and endoglucanase, exogluconase and beta-glucosidase II have been determined. Moreover, the drug likeness and ADMET properties of cellulose II were analyzed for the prediction of pharmacokinetic profiles.
Keywords: ADMET; Cellulose-II; DFT; Molecular Docking; Molecular Modeling